A robotwall simulator - Hor, Keng Seng (University Malaysia Sarawak, UNIMAS., 2005)
This report is written to study the Genetic Algorithm (GA) that applies to the development of mobile robot wall-following behaviors. The purpose of the study is to have a better understanding and a practical experience in robotic fields. GA has presented to be effective procedures for solving wall-following problems. These algorithms are developed for a simulated robot that uses an array of range finders for navigation. It mimics the model of natural evolution has the ability to adaptively search large spaces in near-optimal ways.